Powtarzająca się aluzja do Pindara i misteriów eleuzyńskich we fragmentach komedii Anaksilasa? - Danielewicz, Jerzy (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
Anaxilas in fragments 25 and 30 K.-A. deliberately alluded to Pindar’s fragment 137 S.-M. and the mystery references it contains, but at the same time completely redesigned the sense of the Pindaric phrase for a strong comic effect.